The Validity of Sale and Purchase of Shares in Relation to Nominee Share Ownership (A Case Study of Decision Number 3041K/PDT/2020 and 765PK/PDT/2020) - Nadia, Siska (Jurnal Bina Mulia Hukum, 2024)
The validity of capital injection into the Company and the existence of the shareholder nominee structure are closely related and directly impact legal actions, such as the sale and purchase of shares in the Company. There have been multiple instances concerning the sale and purchase of shares associated with Nominee Share Ownership, a practice commonly encountered in various sectors in Indonesia. This research will focus on two cases, namely Decision Number 3041 K/PDT/2020 and 765 PK/PDT/2020. In addressing these issues, the author is interested in discussing the decisions related to the Nominee Structure in Acquiring Limited Liability Company Share Capital and the Validity of Sale and Purchase of Shares in Relation to Nominee Share Ownership in Cases. This writing is normative legal research. The results of the research show that in the Case based on the Decision discussed, the Sale and Purchase of Shares related to Nominee Share Ownership is invalid and is a form of illegal action because it is contrary to the provisions of Article 48 paragraph (1) of the Company Law that the company must be issued in the name of the actual owner. However, the regulation in Company Law itself does not have an explicit prohibition on the nominee structure of shareholders. The nominee structure as an agreement is only valid and binding for the two parties making the agreement and is not binding on third parties, including not binding on the Company that issued the shares.